Economic impact of foreign labour - Heinz Salowsky (Intereconomics, 1973)
Over 2.3 mn foreign workers are now employed in the Federal Republic of Germany. They account for 10 p.c. of the total labour force. How many foreigners will work in the Federal Republic in future is necessarily a matter for conjecture. Labour market experts forecast that — depending on the rate at which the productive potential is used — between 2 and 2.8 mn foreign nationals will be constantly employed until 1985.
Keywords: 330; Germany